Complex three- dimensional-shaped knitting preforms for composite application. (March 2017) - Hamouda, T
For decades, street lighting and electric poles are made of metal and it is vulnerable to corrosion due to the harsh weather and chemicals. To overcome such essential problems, galvanized iron is used although it adds more hard work to increase the manufacturing cost. Therefore, fiber reinforced polymer lighting pole is proposed. Fiber reinforced polymer materials possess many advantages such as corrosion resistance, high specific strength and stiffness, etc. Two-dimensional woven fabrics and three-dimensional woven fabrics preforms are used to produce composite structures. However, complex shapes cannot be manufactured as a one piece preform. Woven fabrics, whether two-dimensional or three-dimensional need to be cut into patterns to finally produce the complex shapes. These processes add more cost and time to the final composite products. In this research, innovative technique to produce a three-dimensional complex shape knitted preform using regular flat-knitting machine will be presented. Production of such shaped three-dimensional preform permits the production of one piece-shaped preform without any connection or further sewing processes. Produced knitted preform can be used for various reinforcement applications such as light and communication poles, scaffold façades, traffic sign, oars, and wind mill blades.